Improvements in frailty contribute to substantial improvements in quality of life after lung transplantation in patients with cystic fibrosis. Issue 6 (1st April 2020) - Perez, Alyssa A.; Hays, Steven R.; Soong, Allison; Gao, Ying; Greenland, John R.; Leard, Lorriana E.; Shah, Rupal J.; Golden, Jeffrey; Kukreja, Jasleen; Venado, Aida; Kleinhenz, Mary Ellen; Singer, Jonathan P.
Abstract: Background: While lung transplantation (LTx) improves health‐related quality of life (HRQL) in cystic fibrosis (CF), the determinants of this improvement are unknown. In other populations, frailty—a syndrome of vulnerability to physiologic stressors—is associated with disability and poor HRQL. We hypothesized that improvements in frailty would be associated with improved disability and HRQL in adults with CF undergoing LTx. Methods: In a single‐center prospective cohort study from 2010 to 2017, assessments of frailty, disability, and HRQL were performed before and at 3‐ and 6‐months after LTx. We assessed frailty by the short physical performance battery (SPPB). We assessed disability with the Lung Transplant Valued Life Activities scale (LT‐VLA) and HRQL by the Medical Outcomes Study Short Form Physical and Mental Component Summary scales (SF12‐PCS, ‐MCS), the Airway Questionnaire 20‐Revised (AQ20R), and the Euroqol 5D (EQ5D). We tested the association of concurrent changes in frailty and lung function on disability and HRQL by linear mixed‐effects models adjusted for sex and body mass index. Results: Among 23 participants with CF, improvements in frailty and lung function were independently associated with improved disability and some HRQL measures. For example, each 1‐point improvement in SPPB or 200 mL improvement in FEV1 was associated with improved LT‐VLA disability by 0.14 (95%CI: 0.08‐0.20) and 0.07 (95%CI: 0.05‐0.09) points and improved EQ5D by 0.05 (95%CI: 0.03 to 0.07) and 0.02 (95%CI: 0.01‐0.03) points, respectively. Conclusion: Improvement in frailty is a novel determinant of improved disability and HRQL in adults with CF undergoing LTx.